Stress granule-related genes during embryogenesis of an invertebrate chordate - Drago, Laura; Pennati, Alessandro; Rothbächer, Ute; Ashita, Ryuji; Hashimoto, Seika; Saito, Ryota; Fujiwara, Shigeki; Ballarin, Loriano (Frontiers in Cell and Developmental Biology, 2024)
Controlling global protein synthesis through the assembly of stress granules represents a strategy adopted by eukaryotic cells to face various stress conditions. TIA 1-related nucleolysin (TIAR), tristetraprolin (TTP), and Ras-GTPase-activating protein SH3-domain-binding protein (G3BP) are key components of stress granules, allowing the regulation of mRNA stability, and thus controlling not only stress responses but also cell proliferation and differentiation. In this study, we aimed at investigating the roles of tiar, ttp, and g3bp during embryogenesis of the solitary ascidian Ciona robusta under both physiological and stress conditions. We carried out CRISPR/Cas9 to evaluate the effects of gene knockout on normal embryonic development, and gene reporter assay to study the time and tissue specificity of gene transcription, together with whole-mount in situ hybridization and quantitative real time PCR. To induce acute stress conditions, we used iron and cadmium as “essential” and “non-essential” metals, respectively. Our results highlight, for the first time, the importance of tiar, ttp, and g3bp in controlling the development of mesendodermal tissue derivatives during embryogenesis of an invertebrate chordate.